A Straightforward Access to Specific Bisindole Systems Related to Fascaplysin Alkaloids - Chen, Liang; Wang, Zizhen; Li, Yan; Liu, Sheng (Synlett, 2025)
This study presents a a straightforward synthetic approach to the specific pentacyclic bisindole structures related to fascaplysin alkaloids. The key transformation is an acid-promoted cascade involving a C–N bond formation/Mannich-type cyclization/dehydrogenation sequence. Nineteen novel bisindole derivatives bearing a wide range of functional groups were prepared by this method.
Keywords: Fascaplysin; Homofascaplysin C; SnCl4; Cyclization; HFIP